Clinical Manifestation and Diagnostic Approach Towards ‘TORCH Test’: A Knowledge, Attitude and Practice Study - Priyanka Soni; Laxman Kumar Soni; Prabhu Prakash Gupta; Eshank Gupta; Ankita Soni (Journal of Clinical and Diagnostic Research, 2020)
Introduction: ‘TORCH Test’ (Toxoplasmosis, Rubella Cytomegalovirus, Herpes simplex) is usually requisitioned in females having ‘Bad Obstetrics History (BOH)’ or those who are suspicious of ‘intrauterine infection’ or for neonates having congenital malformation. However, the understanding of the test is lacking amongst the practitioners. Hence, this Knowledge Attitude and Practice (KAP) study was conducted to access the knowledge of resident doctors about the correct way of requesting TORCH test. Aim: To assess the understanding, clinical manifestation and diagnostic approach towards TORCH test amongst the Resident Doctors. Materials and Methods: Four groups of questions were put to Resident Doctors from Obstetrics and Gynecology (ObG), Paediatrics (Paeds) and Microbiology Department to assess their understanding of TORCH test. The questionnaire having 30 questions was divided in four groups A, B, C and D. Group A (Q. 1-4) about the fundamental of TORCH infection; Group B (Q. 5-8) brief clinical manifestation; Group C (Q. 9-12) indication of TORCH test i.e., when torch test should be requested and Group D (Q. 13-30) result interpretation of TORCH profile. Results: Questions as to the full form of TORCH test were correctly answered by almost all participants. As far as questions as to Clinical Manifestation, residents of ObG (72.3%) were more accurate in predicting than that of Paeds residents (48%). Amongst Microbiology residents only 5.2% of them were able to gave correct answers. When questions as to when the TORCH test is to be recommended were asked, only 30.7% residents of Paeds, 59% of ObG and 10.5% of Microbiology were aware about it. Interpretation of the test results amongst the participants was also not that up to the mark as only 36.1% in Paeds, 67.6% in ObG and 29.8% in Microbiology residents were correctly able to predict. To sum up, understanding, clinical manifestation and diagnostic approach towards TORCH test is better amongst the ObG residents (67.7%) as compared to that of the Microbiology Residents (26.7%) and Paeds Residents (42%). Conclusion: It can be understood that since the clinical branch residents of ObG and Paeds are not that thoroughly acquainted with the TORCH test understanding and complete clinical information is necessary. Therefore, it is apparent that the same is being not requisitioned in cases where pregnant women or infants have non-descript illnesses where testing is not necessary at all. It is, therefore, highly recommended that regular seminars and teaching activities are conducted by the concerned respective departments in order to impart TORCH test understanding and complete clinical information regarding it.